(untitled) (Impetus, 2021)
Objective: to characterize some processes of the school sports training of the participants in the IV Central American and Caribbean School Sports Games, Armenia, 2013. Materials and methods: quantitative study, with a descriptive and cross-sectional scope. From a universe of 683 participants, a sample of 233 athletes (102 men and 131 women), between 15 and 17 years of age, belonging to nine participating delegations, was intentionally selected, who answered a survey that characterized the processes of school sports training. Results: the majority of students belong to a sports program independent of their educational institution, such as sports clubs, leagues and schools; the sports organization is given mainly by school sports clubs, the main social agent for motivation were the parents. Conclusions: high achievement sports training is not a matter corresponding to educational institutions; It is likely that the representation of the students is not their merit, but rather that of sports entities such as clubs, sports schools and leagues. The main motivating agent was not the physical education teacher, but the parents, other family members, and the coach.